Curator quote / Dr. Muhamad Hafiz Hassan - Hassan, Muhamad Hafiz (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Being the curator of Mapping Sarawak to the World Art Exhibition, hosted at Universitas Trisakti, Indonesia, it is my privilege to introduce this fascinating display of Sarawak’s diverse cultural heritage. The theme of our art exhibition lies in the presentation before the audience of a variety of rather significant Malaysian artworks depicting the essence of one of Malaysia’s states. The entire cross-section is divided into four specific categories and thus provides a viewer with glimpses of Sarawak's spirit. The title ‘Heritage Cultural Buildings’ encourages the viewers to study the gigantic structures that practise the cultures of Sarawak. “Animal” is a collection of music that pays homage to the wildlife found in today’s tropical paradise connected with rainforests and coastal areas. That being said, the word “Botanical” is derived from “botany”, which means the plants, and indeed, there is no shortage of them – from luxuriant rainforest trees to sensitive orchids. Last but not least, this brings viewers close to Sarawak’s people, their traditions and ordinary routine.